Differences in Bioenergetic Metabolism of Obligately Alkaliphilic Bacillaceae Under High pH Depend on the Aeration Conditions - Goto, Toshitaka; Ogami, Shinichi; Yoshimume, Kazuaki; Yumoto, Isao (Frontiers in Microbiology, 2022)
Alkaliphilic Bacillaceae appear to produce ATP based on the H+-based chemiosmotic theory. However, the bulk-based chemiosmotic theory cannot explain the ATP production in alkaliphilic bacteria because the H+ concentration required for driving ATP synthesis through the ATPase does not occur under the alkaline conditions. Alkaliphilic bacteria produce ATP in an H+-diluted environment by retaining scarce H+ extruded by the respiratory chain on the outer surface of the membrane and increasing the potential of the H+ for ATP production on the outer surface of the membrane using specific mechanisms of ATP production. Under high-aeration conditions, the high ΔΨ (ca. −170 mV) of the obligate alkaliphilic Evansella clarkii retains H+ at the outer surface of the membrane and increases the intensity of the protonmotive force (Δp) per H+ across the membrane. One of the reasons for the production of high ΔΨ is the Donnan potential, which arises owing to the induction of impermeable negative charges in the cytoplasm. The intensity of the potential is further enhanced in the alkaliphiles compared with neutralophiles because of the higher intracellular pH (ca. pH 8.1). However, the high ΔΨ observed under high-aeration conditions decreased (~ −140 mV) under low-aeration conditions. E. clarkii produced 2.5–6.3-fold higher membrane bound cytochrome c in the content of the cell extract under low-aeration conditions than under high-aeration conditions. The predominant membrane-bound cytochrome c in the outer surface of the membrane possesses an extra Asn-rich segment between the membrane anchor and the main body of protein. This structure may influence the formation of an H+-bond network that accumulates H+ on the outer surface of the membrane. Following accumulation of the H+-bond network producing cytochrome c, E. clarkii constructs an H+ capacitor to overcome the energy limitation of low aeration at high pH conditions. E. clarkii produces more ATP than other neutralophilic bacteria by enhancing the efficacy per H+ in ATP synthesis. In low H+ environments, E. clarkii utilizes H+ efficiently by taking advantage of its high ΔΨ under high-aeration conditions, whereas under low-aeration conditions E. clarkii uses cytochrome c bound on its outer surface of the membrane as an H+ capacitor.